User experience on Cisco Networking Academy E-Learning platform: a preliminary study - Nordin Saad; Shaliza Hayati A. Wahab; Siti Hasnah Tanalol; Aslina Baharum; Noorsidi Aizuddin Mat Noor (Ubiquity Press, 2020)
E-learning platform is no longer a novelty in this era of globalization. E-learning is becoming more and more popular and can improve the existing learning system. By using the E-learning platform, students will have more options to participate in the courses that are best for them because of the E-learning's ability to accommodate large scale users. Cisco Networking Academy has been implemented in UMS since 2003. However, no preliminary study was conducted to evaluate the implementation in the aspect of user experiences. Therefore, this paper explores end-user experiences in using the platform. An online survey employing 31 participants was conducted to investigate the user experience on Cisco Networking Academy E-learning platform at Faculty of Computing and Informatics for Network Engineering program, Universiti Malaysia Sabah. A modular evaluation of key Components of User Experience (meCUE) used in the structure evaluation of the questionnaires, consists of four modules; Module 1: Product Perceptions, Module 2: User Emotions, Module 3: Consequences of Use, and Module 4: Overall Evaluation. Overall, the Cisco Networking Academy E-learning platform can be well considered. The results show that most students have a positive experience towards the platform in which 58.4% gave positive response of the excellence of the platform (answered Excellent to Very Excellent). Although the findings are in the early stages, it provides a valuable overview of the e-learning platform as one of Malaysia's most common educational platforms.